Diferença não é deficiência: em questão a patologização do fracasso escolar - Doris Anita Freire Costa (1987)
This dissertation aims at showing that children from lower economical levels are in reality "berers" of great potential despite their terribly poor educational performances.In the majority of cases, deficiencies and illnesses are pointed out as the basic causes of their children's poor performances, being considered, above all, from a very pessimistic point of view.If their potential (stemmig from their everyday life experiences)could be stimulated and adequtely taken advante, of, it is possible that their learning and educational performances could improve greatly. A "case study" was done with an alternative group of children showing poor educational performances, at a specialized public instiution.The "life stories" of the reserched subjects point out the contrdictions between their successful performances in everyday ativities and their failure at school.However, a production analysis of these subjects failures at school revels that there does exist an apparent logic bhind their "wrong" answers, and even a certain richness of thought. The determinating factors of the subject's sucess (researched in the acquisition of reading and writing skills) were also anlyzed at the institution to which they were sent. it was verified that these factors re much more related to the organizational methods and to fvourable educational working conditions than to special teachniques, as had been imagined beforehand. We can conclude thet, in order to overcome failure, the learning-teaching process must be based upon the manner of thought and on the reality of the children to which it is directed.Children from very low economical levels